Taman Kota Suropati Sebagai Identitas Kota di DKI Jakarta - Widjaja, Hinijati (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
Currently, many city parks have been renovated but have lost their face, because the design is done instantly, making it difficult to recognize their origins, city parks develop into recreation areas without leaving traces of their history. Departing from the above thoughts, this research was conducted as an effort to map the characteristics of the city park with the study case of Taman Suropati. Taman Suropati has been renovated so that it has lost its face, the design is done instantly, it becomes difficult to recognize its origin, the city park develops into a place of recreation without leaving traces of its history. Departing from the above thoughts, this research was conducted as an effort to map the characteristics of the city park as a city identity, with a case study in Taman Suropati. Currently Taman Suropati has undergone 100% change from its previous form as an identity. Suropati Park was previously a soccer field, no origins or historical traces of the park were found.No trace of the park's history was found, making it difficult to recognize that the park was previously a soccer field.soccer field.Currently Taman Suropati has undergone 100% change from its previous form as an identity. Previously Suropati Park was a soccer field, there are no traces of the origin or history of the park, so it is difficult to recognize that it was previously a soccer field. A hidden soccer player sculpture cannot be a clue to the origin of the park, the absence of markers that provide information about the origin of the park makes visitors lose track of the origin of Taman Suropati. But on the other hand with the diversity of facilities that are provided. Taman Suropati is able to build vitality for the area, as well as culinary tours at night, Taman Suropati has been able to become a generator for its environment. From this description, Taman Suropati can become an identity within the framework of the environment or medium level, namely as a place identity. The results showed that the city park can be a city identity in various contexts, namely the global context (provincial level), the context of urban planning or macro level (region), the context of the environmental framework as a place identity. Keywords: City Park, Identity, Taman Suropati, Jakarta